Virtual Orientation Overrides Physical Orientation to Define a Reference Frame in Spatial Updating - He, Qiliang; McNamara, Timothy P. (Frontiers in Human Neuroscience, 2018)
Previous studies showed that people could use either an egocentric or allocentric reference frame in spatial updating with body-based cues (i.e., physical body movements), but the adopted reference frame was anchored by the physical egocentric front when body-based cues were constrained. A recent study (He, McNamara, & Kelly, 2018) showed that even without body-based cues, the orientation participants initially faced in the virtual environment (initial heading) could be used to establish a reference frame, suggesting that the physical egocentric front could be overridden by a virtual orientation. In the current project, we aimed to (a) replicate He et al.’s finding, (b) examine when the reference frame defined by the virtual initial heading was established, and (c) investigate the cognitive processes in establishing the initial heading as a reference frame. In four experiments, we were able to replicate the previous findings and found that the reference frame defined by the initial heading was established during spatial updating. More importantly, the reference frame defined by the initial heading was egocentric and participants did not need to know the orientation of their initial heading at the beginning of spatial updating to be able to use it. We discuss the cognitive processes of reference frame selection in spatial updating when body-based cues are absent.